Buffalo wings - Reynolds, Aaron, 1970- (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
While searching for the perfect Super Bowl snack, Rooster comes across a recipe for Buffalo wings and, before reading it completely, goes in search of what he believes is the missing ingredient.